Vocal Cord Palsy and Neutropenia: : Unusual Presentation of B-12 Deficiency in Adult Patient, A Case Report - Alharbi, Abdulmajeed (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.